Media Criminology – The role of the media and its influence on contemporary society - Santos, Francisco Falkembach dos (Seven Editora, 2024)
This study explores the role of media criminology and its influence on contemporary society, emphasizing the portrayal of crime and penal justice by the media. It aims to clarify the significant consequences of media representations on public perception of crime and justice. Our research methodology is grounded on an extensive review of significant literature, avoiding direct quotes but emphasizing the importance of understanding media's role in shaping societal perspectives. The study reveals that media, through its depictions of crime, significantly influences public perception and understanding of criminal justice. Moreover, we found that the evolution of technology, specifically social media, plays a substantial role in media criminology. We conclude by asserting the crucial necessity for a critical understanding and questioning of media representations of crime in our contemporary society. DOI:https://doi.org/10.56238/sevened2023.006-152